THE EFFECTS OF KINESITHERAPY IN PRESERVING FUNCTION IN CHILDREN WITH CEREBRAL PALSY - Constantinescu Mihai (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
The case study presented highlights the pathological physiological genesis and evolutionary dynamics of different neurogenic diseases which in most cases can cause changes in the neuro-myo-arthro-kinetic apparatus such as functional incapacity through installed paralysis. Repercussions of neurological conditions are also harmful to the normal function and n development of the neurological child, the earlier the disease is established or the greater the complexity of the neurological pathology. Physical therapy through the variety of methods and techniques used judiciously can lead to the realization of a program for the preservation of somatic-functional structures, preventing their deconditioning